SF-36 metric as a diagnostic aid for conversion disorder - Karantay Mutluay, Fatma; Yeni, N. (Springer Heidelberg, 2014)
[Abstract Not Available]
Joint Congress of European Neurology -- MAY 31-JUN 03, 2014 -- Istanbul, TURKEY
WOS: 000347674000505
Keywords: Conversion Disorder; Diagnostic Aid; SF-36 Metric